Pengaruh Quality Of Work Life dan Profesionalisme Terhadap Keterlibatan Kerja Personil Satlantas Di Kepolisian Resort Kota Besar Medan - Ricky Ananda Marpaung; Saiful Ahyar Lubis; M. Rajab Lubis (Mahesa Research Center, 2022)
The purpose of this research is to see: The influence of quality of work life and professionalism on the engagement of satlantas personnel in the Police Resort Kota Besar Medan. Hypothesis proposed is there is an influence of quality of work life and professionalism on work engagement. The research was conducted on 65 Satlantas personnel with sampling techniques is purposive sampling. Data retrieval by scale method is the scale of work engagement, quality of work life scale and professionalism scale. The data is analyzed by multiple regression statistics. The results showed; 1). There is a significant influence between quality of work life and professionalism on Work Engagement, the value of the Coefficient freg = 42,113; correlation coefficient R = 0.703; p < 0.000. Thus the research hypothesis is accepted, there is an influence between the quality of work life and professionalism with work engagement. The total effective contribution of independent variables (quality of work life and professionalism) to work involvement is 46.4%. From these results it is known that there are still 53.6% of the influence of other factors on work engagement which is not seen in this study. 2). There is a significant influence between Quality Of Work Life on work engagement, with a correlation coefficient of 0.547; this means that the better the Quality Of Work Life, the better work engagement. Quality Of Work Life provides an effective contribution to the Work Involvement variable or the equivalent of 17.2%.3). There is a significant influence between professionalism and job involvement with a correlation coefficient of 0.646; this shows, the higher the professionalism, the better the Work Involvement of the Medan Police Traffic Police Personnel, and conversely, the lower the professionalism, the lower the work engagement. The professionalism variable gave an effective contribution to the Work Engagement variable by 32.3%.